Transformasi SDM Akademik: Membangun Perguruan Tinggi Berdaya Saing Global - Yosafat Fonataba; Esau Hombore; Ivone Agustina Nathan; Simon Yanuarius Konorop (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to develop a model of academic human resource (HR) transformation based on competency, research, and digitalization to improve the competitiveness of Private Higher Education Institutions (PTS) in Merauke. Using a qualitative approach through case study and mixed-methods methods, this study examines the challenges and strategies for optimizing academic HR management. Data were collected through in-depth interviews with PTS leaders, lecturers, and education staff, as well as participant observation, quantitative surveys, and documentation studies. The results of the study indicate that academic HR management in PTS Merauke faces various challenges, such as limited access to professional training, minimal research facilities, and low incentives for scientific publications. External factors, such as budget constraints and low levels of academic collaboration, also worsen the condition of HR development. To overcome these challenges, this study recommends a strategy to improve academic competency through continuous training, research incentives, and optimization of digitalization in learning and academic administration. The application of a HR management model based on competency, research, and technology is expected to improve the effectiveness of education, academic productivity, and the competitiveness of PTS Merauke at the national and global levels. By strengthening an inclusive and innovative academic ecosystem, higher education institutions in remote areas can be more adaptive to change and are able to produce quality and highly competitive academic staff.